Impact of drill bit wear on temperature increase in dental implant osteotomy: an in vitro study. - Marco Sorgato; Anna Bottin; Michele Stocchero; Marco Toia; Enrico Savio (PLoS ONE)
Objectives Dental implant surgery relies extensively on bone drilling, a critical procedure with intrinsic challenges. Drill bits show significant wear and are frequently utilized beyond the manufacturer's recommended limits. Such practices can result in adverse effects, including friction and temperature rise in the surrounding bone area during interventions, with an increased risk of necrosis that can compromise the dental implant osseointegration. This study aimed to compare the quality of osteotomy obtained from two different protocols to determine a possible correlation between the drilling temperature and the tool wear and to evaluate their impact on potential health damage. Materials and methods Experimental evaluations were conducted using synthetic bone that reproduced human bone characteristics. The drilling phase involved real-time temperature acquisition and scanning electron microscopy analysis of tool wear evolution. After the operation, actual hole size and geometry were characterized using a coordinate measuring machine, and temperatures and torques were measured during the subsequent implantation phase. Results The findings revealed a direct correlation between tool wear and the temperature rise during the drilling phase, while a lower correlation was found with the hole profile geometry variation. The implantation phase demonstrated temperature and torque values within acceptable ranges. Conclusions This study highlights the importance of adhering to proper tool maintenance and replacement protocols. By following recommended guidelines, practitioners can minimize adverse effects and enhance the success of dental implant procedures.